The Role of P2K2 Companions for Financial Management and Family Business Plans in the Family Hope Program in Makassar City - Mita Arnika; Irfan B (Newinera Publisher, 2023)
The future growth of the wheel of life will greatly benefit from innovative program policies, which will have a positive impact on the economy. However, it is important to acknowledge that many individuals, particularly those from impoverished households, may face economic challenges owing to a lack of community knowledge. This phenomenon is primarily caused by a decrease in financial literacy and a lack of proficiency in financial management, which therefore leads to potential future challenges. The author proposed the implementation of P2K2 Activities as a solution to the problem. This event took place as one of the supplementary responsibilities in Makassar City, namely carrying out P2K2 in the community. This activity offers fundamental information and abilities in the management of revenue and spending, as well as the development of company plans. The approach employed involves outreach and training sessions for PKH participants. The anticipated outcome of this service is that conducting this activity will yield improved financial outcomes for households impacted by the epidemic.